Parvovirus infection in children - V. A. Anokhin; A. M. Sabitova; T. A. Aglyamova; E. Y. Minaeva; N. A. Marchenkova; O. Y. Knyazeva (LLC "Diagnostics and Vaccines", 2019)
The article presents current information about the etiology, epidemiology, clinical manifestations of parvovirus infection in children. The problems of the use of laboratory tests, treatment and prevention ofinfection.